Percepções de médicos residentes em clínica médica em relação ao atendimento de pacientes psiquiátricos - Santana, Paulo Roberto Oliveira Henrique (2020)
It is a known fact that physicians have difficulties providing medical care to patients with psychiatric disorders and, sometimes, display negative feelings and social stigmas towards such patients. This study aims to assess the mental healthcare education offered to resident physicians participating in the Medical Practice Program of the Medical Sciences and Health College - FCMS (Faculdade de Ciências Médicas e Saúde) at PUCSP and analyze the feelings, perceptions and stigmas displayed by these doctors when faced with the care of patients with mental disorders. This is a qualitative, quantitative, descriptive and cross-sectional study. We invited all the resident doctors studying the first or second year of the Medical Practice Course at the FCMS at PUC (n=36) and 32 of these participated in the study. The study applied quantitative instruments: one for outlining the social and demographic profile of the participants and the Brazilian version of the validated attribution questionnaire (AQ-26B0). The qualitative data were obtained by the focal group technique performed on 14 of the resident physicians, chosen by convenience, and afterwards, the appreciation of the results was done by using Pareto charts and Bardin’s content analysis. All the procedures were conducted only after approval by the Ethics in Research Committee in FCMS at PUC-SP (CAAE 01561518.7.0000.5373). the results show that the residents in Medical Practice display more stigmas in aspects such as fear and intolerance and report gaps in their education, low perception of responsibility with care and difficulties to legitimize the complaints from patients with mental disorders. It is possible to conclude that there is a need for educational interventions that will lead to the reduction of stigmas and the search for training in integral and empathic care towards people who suffer from mental disorders